Interleukin-1β Induces mtDNA Release to Activate Innate Immune Signaling via cGAS-STING - Aarreberg, Lauren D. (Mol Cell, 2019)
Interleukin-1 beta (IL-1β) is a pleiotropic mediator of inflammation and is produced in response to a wide range of stimuli. During infection, IL-1β production occurs in parallel with the onset of innate antimicrobial defenses, but the contribution of IL-1β signaling to cell-intrinsic immunity is not defined. Here, we report that exogenous IL-1β induces interferon regulatory factor 3 (IRF3) activation in human myeloid, fibroblast, and epithelial cells. IRF3 activation by IL-1β is dependent upon the DNA-sensing pathway adaptor, stimulator of interferon genes (STING), through the recognition of cytosolic mtDNA by cyclic guanosine monophosphate (GMP)-AMP synthase (cGAS). IL-1β treatment results in interferon (IFN) production and activation of IFN signaling to direct a potent innate immune response that restricts dengue virus infection. This study identifies a new function for IL-1β in the onset or enhancement of cell-intrinsic immunity, with important implications for cGAS-STING in integrating inflammatory and microbial cues for host defense.